2020
DOI: 10.1140/epjc/s10052-020-08495-6
|View full text |Cite
|
Sign up to set email alerts
|

Dark photon dark matter and fast radio bursts

Abstract: The nature of dark matter (DM) is still a mystery that may indicate the necessity for extensions of the Standard Model (SM). Light dark photons (DP) may comprise partially or entirely the observed DM density and existing limits for the DP DM parameter space arise from several cosmological and astrophysical sources. In the present work we investigate DP DM using cosmic transients, specifically fast radio bursts (FRBs). The observed time delay of radio photons with different energies have been used to constrain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…For example, upgraded LSW experiments [195][196][197], experiments using atomic transitions [125,198,199], or Aharanov-Bohm experiments [200,201] may improve the purely-laboratory bounds on DPs. Whereas searches using X-ray [202] and radio [203,204] telescopes, fast radio burst timing [205], or asteroseismology [206], may improve upon existing astrophysical bounds.…”
Section: E Optimising Future Experimentsmentioning
confidence: 99%
“…For example, upgraded LSW experiments [195][196][197], experiments using atomic transitions [125,198,199], or Aharanov-Bohm experiments [200,201] may improve the purely-laboratory bounds on DPs. Whereas searches using X-ray [202] and radio [203,204] telescopes, fast radio burst timing [205], or asteroseismology [206], may improve upon existing astrophysical bounds.…”
Section: E Optimising Future Experimentsmentioning
confidence: 99%
“…They concluded that f DM in MACHO is constrained to < 0.001 when there were no search of multiplepeaked FRBs for time intervals larger than 1 ms and flux ratio less than 10 3 . These methods of using FRBs to find dark matter in MACHO is widely studied later [261][262][263][264][265].…”
Section: Hubble Parameter H(z)mentioning
confidence: 99%
“…Many authors [3][4][5][6] propose to discuss rotation curves of spiral galaxies with a spin integral S via gravi-magnetic fields or spin-spin interactions in general relativity (GR) to avoid the dark matter mystery. Despite a lot of thematic discussions and research efforts, the dark matter problem is still "one the biggest puzzles in cosmology" [7].…”
Section: Introductionmentioning
confidence: 99%